IMPLIKASI PUTUSAN VERSTEK PADA PEMANGGILAN PARA PIHAK: ANALISIS TANGGUNG JAWAB HUKUM KELURAHAN DI KOTA PALU - Suhri Hanafi; Ahmad Arief (Fakultas Syariah Institut Agama Islam Negeri Palu, 2019)
Summons in the civil procedural law is to submit to the parties formally and properly related to the case in court, in the delivery procedure of a summons once the parties are not found, then the village head or Lurah is given the mandate to deliver it to the litigant. The results of research conducted on the village in Palu do not even have a procedure for accepting and submitting willingly, it is caused by the ignorance of the village regarding the obligation to submit summons, besides the village feels has no interest in the bailiff’s primary task. Analysis of village’s legal responsibility in the summoning function can be categorized as collective responsibility on the subject side, whereas from the other side, object side, it is a type of absolute accountability.